Comparative Growth Performance and Nutrient Utilization in Commercial Broiler Chickens fed Diets Supplemented with Herbal Methionine vis-Ã -vis Synthetic DL-Methionine during Summer Season - Tiwari, Devendra Prasad (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted to discern the comparative effects of dietary supplementation of herbal methionine and synthetic DL-methionine on growth performance and nutrient utilization in broiler chicks during summer season. A total of 180, day-old commercial broiler chicks were divided randomly into 6 treatment groups with 3 replicates each and 10 broiler chicks per replicate. There were 6 dietary treatments viz., treatments T1 (control, basal diet without methionine supplementation), T2 (basal diet supplemented with 0.2 % synthetic DL-methionine), T3 (basal diet supplemented with 0.15 % synthetic DL-methionine + 0.05 % herbal methionine), T4 (basal diet supplemented with 0.1% synthetic DL-methionine + 0.1% herbal methionine), T5 (0.05% synthetic DL-methionine + 0.15 % herbal methionine) and T6 (basal diet supplemented with 0.2% herbal methionine). The feeding trial lasted for 42 days viz., 0-21 days (starter phase) and 21-42 days (finisher phase). Weekly body weight and feed intakes were recorded for each treatment group of broiler chicks. A metabolism trial was also conducted during the 6th week of feeding trial. During starter phase (0-21 days) the body weight gains were 576.20, 611.33, 598.13, 606.93, 596.10 and 636.09 g, respectively, in treatment groups T1, T2, T3, T4, T5 and T6 and there was significantly (P